Analisis Indeks Kepuasan Masyarakat Terhadap Kualitas Pelayanan Pada Badan Pengelolaan Keuangan Dan Aset Daerah Kabupaten Kutai Kartanegara - Raharjo, Sugeng; Suprapto, Heru (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2017)
This research was conducted at the Regional Finance and Asset Management Agency of Kutai Kartanegara Regency. This study aims to measure the level of public satisfaction with services that have been done by BPKAD Kukar. To measure the level of satisfaction is used Public Satisfaction Index as listed in the Ministerial Regulation No.16 of 2014. This study used 43 respondents consisting of various elements of both community organizations, business, and government. From the results of the study showed that the value of the Satisfaction Index showed good condition or with score average of 2.91 with 4 scale or equal to 69,69 with 100 scale. The value of IKM and IKM Conversion Intervals indicates that the Quality of Service in BPKAD falls into Category B with Good Service Unit Performance indicating that the quality of BPKAD Kukar service is in good categoryKeywords : Index of Public Satisfaction, Service